(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Looking closer at how consumer buy things on Myntra, an Indian online hub for clothes and lifestyle goods, reveals what really influences their choices. Price often tops the list, though quality holds strong weight, too. Discounts grab attention fast, yet brand reputation significantly shapes long-term loyalty. Customer feedback and reviews can build trust or spark doubt. A smooth application interface keeps users around longer than clumsy ones tend to. Ads seen on social platforms encourage some toward checkout without them even planning to. Young buyers act differently from older groups; young consumers are influenced by what is trending in the market whereas older consumers look for quality and durability. Seasonal sale events bring waves of activity that few other triggers match. Suggestions tailored to past clicks sometimes feel oddly spot-on. Returning items with little hassle removes one big worry mid-purchase. A fresh look at data came from surveys, online tools, printed material, web pages, and academic papers. Results are meant to help store owners, promotion teams, and companies improve shoppers' experience and build trust. Work adds depth to online selling strategies while clarifying how buyers act using sites such as Myntra.